Parametrization of Bending Moments in Creep Analysis of Circularly Symmetric Simply Supported Plates - Białkiewicz, J. (Engineering Transactions, 1984)
This work presents the method of the solution, based on the parametrization of the bending moments, for annular simple-supported plates. As a result of this parametrization, the solution of the boundary problem is reduced to the solution of three ordinary differential equations of the first order. The set of equations separated with respect to the derivative of unknown functions makes it possible to apply the standard Runge-Kutta integral procedures. The time of the first cracks will be calculated using the Kachanov-Rabotnov damage law.